ANALISIS SISTEM PENGENDALIAN INTERN ATAS PERSEDIAAN BARANG DAGANG (Studi Pada Koperasi Pegawai Republik IndonesiaUniversitas Negeri Malang) - Arif Sugianto; Farah Adiba (JOURNAL AKSES STIA MALANG, 2020)
All coordinated activities to achieve the main goal of a company, one of with the internal control system.The internal control system includes the organizational structure, the procedure, the measurement arecoordinated to keep organization`s wealth, check the precision and the realibility of accounting data,as well as stimulate the efficiency and comply with management policy. This research focused on theinternal control system analysi of inventory on KPRI State University Of Malang.In conducting this research, author uses collecting data method such as interview, observation, and thenanalyze use literature study, as well as using the method of documentation. This research based oninventory accounting system theory. Inventoryaccounting system can be explained by flowchart.Based on result, it can be concluded that the system exist in KPRI State University Of Malang is stillhaving weakness. They are double assignment in the organization system,the minimum document andinformation system used in KPRI State University Of Malang. The aim of this research to analyzeapplication of the internal control system of inventoryon KPRI. This analysis do to solve problemoccurred on KPRI, so this research canminimize errors against application of the internal controlsystem of inventory